2021
DOI: 10.1109/lra.2020.3044029
|View full text |Cite
|
Sign up to set email alerts
|

Task-Oriented Motion Mapping on Robots of Various Configuration Using Body Role Division

Abstract: Many works in robot teaching either focus on teaching a high-level abstract knowledge such as task constraints, or low-level concrete knowledge such as the motion for accomplishing a task. However, we show that both high-level and low-level knowledge is required for teaching a complex task sequence such as opening and holding a fridge with one arm while reaching inside with the other. In this paper, we propose a body role division approach, which maps both high-level task goals and low-level motion obtained th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…In a typical LfO system, a task is defined as the transition of a target object; for example, a contact state between polyhedral objects for part assembly by [1] or a topology of a string for tying a knot by [2]. To extend the LfO to household actions, [8] recently reported an LfO system that supports motion constraints derived from the linkage mechanism and the task representations were mapped on robots of various configuration by [9]. Although these previous systems achieved success in specific task domains, the tasks were defined with physical constraints; semantic constraints were ignored.…”
Section: Representation Of Motion Constraints In Robot Teaching Frame...mentioning
confidence: 99%
“…In a typical LfO system, a task is defined as the transition of a target object; for example, a contact state between polyhedral objects for part assembly by [1] or a topology of a string for tying a knot by [2]. To extend the LfO to household actions, [8] recently reported an LfO system that supports motion constraints derived from the linkage mechanism and the task representations were mapped on robots of various configuration by [9]. Although these previous systems achieved success in specific task domains, the tasks were defined with physical constraints; semantic constraints were ignored.…”
Section: Representation Of Motion Constraints In Robot Teaching Frame...mentioning
confidence: 99%
“…for the local tightening policy, the robot needs to pay attention to the continuous feeding in the direction coaxial to the central axis of the bolt until tightening while meeting the collision conditions of the local approach sub-policy. In order to evaluate the coaxiality error between the end tool and the bolt, Equation (11) calculates the distance between the key points on the end tool and the straight line where the bolt is located, and takes the maximum of the two as the evaluation value. At the same time, considering the feed of the end tool along the central axis of the bolt, the position error for the end tool is used to characterize it.…”
Section: Local Tighteningmentioning
confidence: 99%
“…It can also leverage the experience more effectively, resulting in significant performance gains. Sasabuchi and Wake et al [11] propose a body role division method suitable for different robots. It guides the configuration of the robot to complete a given task, which helps to teach a series of task sequences.…”
Section: Introductionmentioning
confidence: 99%
“…One of the frameworks to address this difficulty is Learning-from-Observation (LfO), in which a human provides manipulation instruction to a robot through a oneshot demonstration [1], [2]. We have previously shown that the LfO framework can be used to teach the humanoid robot implicit high-level knowledge for the task, such as the semantic and physical constraints that exist between the environment and the grasping object, and the reaching body posture that is less likely to conflict with the environment [3]. Planning grasps based on these implicit knowledge has the potential to realize task-grasping.…”
Section: Introductionmentioning
confidence: 99%